Rozwiąż nierówność:

a) 9 - 4x² > 0
b) (x - 5)² -2(x -5) ≤ 0
c) -2(x +√2)(2x - √2) > 0
d) 8x - 2√2x² < 0
e) x² -2x + 2 ≤ 0
f) 7x - 4x² - 4 ≥ 0
g) 3x2 - 11x - 20 > 0
h) 64x² + 49 ≥ 0
i) x² - 4 < 4
j) x² ≥ 9
k) x² ≤ -4

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T12:16:13+02:00
A) -4x²>-9/(:-4)
x²>9/4
x> √9/4
x>1½ lub x> -1½
b) x²-10x-2x+35≤0
x²-12x+35≤0
Δ=b²-4ac
Δ=144-140=4
√Δ=2
x₁=-b-√Δ/2a
x₁=10/2=5
x₂=-b+√Δ/2a
x₂=14/2=7
x∈<5,7>
c) -2(2x²+√2x-2)<0
-4x²-2√2x+4<0
Δ=8+64=72
√Δ=6√2
x₁=½√2
x₂=-√2
x∈(-√2,½√2)
d) -2√2x²+8x<0
x(-2√2x+8)<0
x=4√2
x=0
odp. x∈(-oo,0) v (4√2,+oo)
e) x²-2x+2≤0
Δ=0
x=1
odp/ x∈{1}
f) -4x²+7x-4≥0
Δ=-15, sprzeczność
brak miejsc zerowych
odp. x∈Ф( zbiór pusty)
g) 3x²-11x-20>0
Δ=361
√Δ=19
x₁=-1⅓
x₂=5
odp. x∈(-oo,-1⅓)v(5,+oo)
h) 64x²+49≥0
64x²≥-49/(:64)
x²≥-49/64,sprzeczność ( nie ma pierwiastka z liczby ujemnej)
odp.x∈Ф
i)x²-4<4
x²<8
x<2√2 v x<-2√2
odp.x∈(-2√2,2√2)
j) x²≥9
x≥3 v x≥-3
odp.x∈(-oo,-3> v <3,+oo)
k) x²≤-4 sprzeczność,(to co w przykładzie h)
odp.x∈Ф( do zbioru pustego)
1 1 1